PHYSICAL STABILITY TEST AND ETHANOL CREAM IRRITATION TEST OF Moringa oleifera L. - Nining Sugihartini; Zainab Zainab; Aji Pamungkas (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The development of topical dosage forms of Moringa leaf extract cream has been carried out because of its properties that can moisturize the skin. A pharamceutical preparation must meet the requirements of stability and non toxic. The study aimed to determine the effect of variations un the concentration ethanol extract cream of Moringa leaf of physical stability and irritability. Ethanol extract of Moringa leaves was obtained by maceration method with 50% ethanol solvent. The extract was then formulated in the form of O/W base scarring with concentrations of 1% (F1), 3% (F2), and 5% (F3). Creams were evaluated for physical stability including mechanical tests (centrifugation) and physical stability at room temperature (25 Ã‚Â± 2oC) with parameters pH, viscosity on days 1, 7, 14, 21 and 28. In addition, creams were also evaluated for their irritability in vivo with using test animals (rabbits). The data obtained were analyzed using one-way ANOVA test. The results of the physical stability test showed that an increase in the concentration of Moringa leaf extract caused an increase in viscosity (P <0.5) and a decrease in pH (P <0.5) but did not affect physical stability (mechanical test) and its irritating effect. F2 (1%) has a pH of 7.61 while F4 (5%) is 7.01. Based on the results of the study, it is concluded that variations in the concentration of ethanol extract of Moringa leaves can affect the physical stability of the cream and do not affect its irritation properties. Moringa leaf ethanol extract cream with a concentration of 5% (F4) has physical stability and does not irritate the skin better than other formulas. Keywords: extract of moringa leaves, cream, physical properties test, irritation test, stability